Digital Technology, Storytelling, and Ecosystem Challenges in Promoting Traditional Batak Cuisine as a Tourist Attraction in Simalungun Regency - Iwan Riady; Zulkhaidir Pohan (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2026)
This study examines the role of digital technology in promoting traditional Batak cuisine as a tourist attraction in Simalungun Regency, but requires effective promotional strategies in the digital age. This study aims to examine the role of digital technology in promoting traditional Batak cuisine and to analyze the key enabling and constraining factors influencing its utilization among local culinary businesses. The study used a qualitative descriptive approach by observation, in-depth interviews, and documentation. The research informants consisted of 13 people. The data were analyzed using the thematic analysis. The results showed that digital technology plays a significant role as an enabler in promoting traditional Batak cuisine through four main dimensions: (1) amplifying visibility through social media; (2) democratizing access; (3) interactivity and engagement building; (4) digital storytelling. Meanwhile, the barriers include limited digital literacy, especially among the older generation, limited capital for digital investment, uneven Internet infrastructure in rural areas, limited time and human resources, content competition and platform algorithm changes, difficulty in measuring ROI, the risk of authenticity distortion, and a lack of coordination among stakeholders. This study concludes that digital technology plays a vital role in promoting Batak traditional cuisine as a tourist attraction, but its success depends on an ecosystem involving various stakeholders and requires a balanced strategy between digital innovation and cultural authenticity preservation.